OUTCOMES OF TREATMENT OF CHOROIDAL NEOVASCULARIZATION ASSOCIATED WITH CENTRAL SEROUS CHORIORETINOPATHY WITH INTRAVITREAL ANTIANGIOGENIC AGENTS. Issue 12 (December 2015) - Chhablani, Jay; Kozak, Igor; Pichi, Francesco; Chenworth, Megan; Berrocal, Maria H.; Bedi, Rumneek; Singh, Rishi P.; Wu, Lihteh; Meyerle, Catherine; Casella, Antonio Marcelo; Mansour, Ahmad; Bashshur, Ziad; et al.
Abstract : Purpose: To report clinical characteristics and treatment outcomes from the largest case series of choroidal neovascularization secondary to central serous chorioretinopathy. Methods: Retrospective analysis of 46 eyes of 43 consecutive subjects. Collected data included demographic details, history of presenting illness, clinical examination details including visual acuity at presentation and follow-up with imaging and treatment details. Main outcome measures were the proportion of eyes that had improved (3 or more lines), stable (within ±1 line), or decreased (3 or more lines) vision at the final visit as compared with baseline examination. Secondary efficacy outcomes included change in visual acuity at final follow-up, number of injections, treatment-free interval, and adverse events. Results: Mean age was 57.56 years (range 29–79 years). Mean follow-up duration was 38.3 months ± 58.9 months. More than 3 lines of improvement in 12 eyes (26%), vision was stable (within ±1 line) in 19 eyes (41.3%), and >3 lines of loss was noted in 6 eyes (13%). Mean change in the number of lines was 1.16 ± 3.74. Mean number of anti-vascular endothelial growth factor injections during the follow-up was 4.45 ± 4.1. The longest treatment-free interval was 8.9 months ± 7.5 months. There were no adverse events noted. Conclusion: Anti-vascular endothelial growth factor therapy as a primary therapy for choroidal neovascularization secondary to central serous chorioretinopathy is safe and efficacious, without any serious adverse events. Abstract : This multicenter retrospective study reports anti-vascular endothelial growth factor monotherapy safe and efficacious for choroidal neovascularization secondary to central serous chorioretinopathy, without any serious adverse events. Mean number of anti-vascular endothelial growth factor injections during the follow-up was 4.45 ± 4.1. The longest treatment-free interval was 8.9 months ± 7.5 months.